STRATEGI POLITIK CALON LEGISLATIF TERPILIH PARTAI KEADILAN SEJAHTERA (PKS) PADA PEMILIHAN UMUM LEGISLATIF DI KOTA PEKANBARU TAHUN 2024 - Indra, Aswela; ,, Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
General elections are a democratic mechanism that enables citizens to elect representatives who will voice their aspirations in parliament. In the context of the 2024 election in Pekanbaru City, the Prosperous Partai Keadilan Sejahtera (PKS) successfully retained its seats in the regional parliament by implementing various political strategies. This study aims to analyze the offensive and defensive strategies employed by Partai Keadilan Sejahtera (PKS) candidates in winning the election. This research utilizes a descriptive qualitative method with in-depth interviews and document analysis. Primary data was obtained from interviews with legislative candidates and party officials, while secondary data was sourced from journals, news articles, and related documentation. The results of the study show that the strategy used by the Prosperous Justice Party legislative candidates in the field is in accordance with Peter Schorder's political strategy theory, which refers to an offensive approach to expand support and a defensive strategy to maintain loyal voters. With this strategy, the Partai Keadilan Sejahtera(PKS) managed to maintain its seat in the Pekanbaru City DPRD in the 2024 general election where the offensive strategy was carried out through a community- based campaign with a direct approach such as home visits and aspiration houses, as well as education to voters regarding legislative functions and a defensive strategy relying on track records and programs that have been running, while closing the voter market that is vulnerable to money politics by emphasizing integrity and real performance. Keywords: election, political strategy, prosperous justice party